(untitled) (Altre Modernità, 2022)
The paper is dedicated to the analysis of digital tools used in the teaching and lexicography of Serbian as foreign language. Considering the particular characteristics of this language, especially in relation to its rich morphology, the essential tools in the early stages of study include morphological dictionaries, while at the intermediate and advanced levels digital dictionaries and linguistic corpora are necessary. Unlike English, which in terms of digital technologies is being updated and developed almost continuously, languages with fewer resources, such as Serbian, mainly make use of traditional tools, and only in recent years has the tendency to orient themselves towards digital. The global pandemic, which exploded in early 2020, has accelerated this process by urging teachers to search for innovative paths that lend themselves to virtual teaching. The questions listed here and for which we will try to find an answer concern: digital tools for the Serbian as foreign language, their advantages over traditional teaching material, the possible ways to follow in experimenting with the Data-driven learning methodology.